Exploring the Role of Communication in Enhancing the Gastronomic Tourism Experience - Mwangi, Grace; Mwalongo, Joseph (Tecno Scientifica Publishing, 2023)
This article highlights the increasing prevalence of gastronomic tourism, which emphasizes tasting local cuisine and experiencing local culinary culture. In terms of language, culture, and cuisine, the significance of effective communication in facilitating this experience is emphasized. The article explains that translation applications and social media are playing an increasingly significant role in how travellers communicate with natives. Effective communication is regarded as essential for a successful gastronomic tourism experience, as it enables tourists to interact with local communities and develop a deeper appreciation for culture and cuisine. Additionally, the article highlights the significance of sustainable and responsible gastronomic tourism policies, which can promote locally sourced and diverse cuisines, responsible consumption, and support local food producers and suppliers. Gastronomy is an essential element of a region's cultural heritage, and it has a substantial impact on tourism, job creation, and economic development. Gastronomy plays a significant role in attracting travellers and enhancing the overall tourism experience of destinations.